Impact of Geomagnetically Induced Currents on High Voltage Transformers in Malaysian Power Network and Its Mitigation - Khurshid Z.M.; Ab Aziz N.F.; Rhazali Z.A.; Ab Kadir M.Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer aided design; Earth (planet); Electric grounding; Electric power transmission networks; Geomagnetism; Power transformers; Short circuit currents; Solar energy; Timing circuits; Transformer protection; Circuit faults; Computational modelling; Direct-current; Electro-magnetic transient; Geomagnetic disturbance; Geomagnetically induced currents; High-voltage transformers; Malaysian power network; Malaysians; Power networks; Power system computer aided designs; Power system computer-aided design for electromagnetic transient including direct current; PSCAD; Software; Space weather; Electric network analysis